Interactive PowerPoint in Indonesian Language Learning In Elementary Schools: A Systematic Literature Review - Mirda Delita; Yasinta Mahendra; Rohmani; Berta Apriza (Journal for Lesson and Learning Studies, 2025)
The rapid development of information and communication technology has significantly transformed the field of education, including the approach to teaching Indonesian language in elementary schools. A key challenge in Indonesian language learning is the low level of student interest and motivation, often caused by conventional and less engaging instructional methods. This study aims to critically analyze the effectiveness of using interactive PowerPoint media in enhancing the quality of Indonesian language learning processes and outcomes. The research employed a systematic literature review method, analyzing a selection of relevant scholarly articles published within the last five years. Data analysis was conducted qualitatively using thematic synthesis to identify recurring patterns and the impact of PowerPoint media on various learning aspects. The findings reveal that interactive PowerPoint media positively influence students’ learning motivation, conceptual understanding, and overall academic performance. Visual elements such as images, animations, and interactive transitions were found to effectively capture students’ attention and encourage active participation in the learning process. The study concludes that interactive PowerPoint is an effective instructional tool to support more meaningful and student-centered Indonesian language learning. These findings imply the importance of technological innovation in instructional design to enhance student engagement and optimize learning outcomes.